Making football safer for women: a systematic review and meta-analysis of injury prevention programmes in 11 773 female football (soccer) players - Crossley, K. M.; Patterson, B. E.; Culvenor, A. G.; Bruder, A. M.; Mosler, A. B.; Mentiplay, P. F. (British Journal of Sports Medicine, 2020)
Objective To evaluate the effects of injury prevention programmes on injury incidence in any women`s football code; explore relationships between training components and injury risk; and report injury incidence for women`s football.